Proinflammatory cytokine and cytokine receptor gene expression kinetics following challenge with Flavobacterium psychrophilum in resistant and susceptible lines of rainbow trout (Oncorhynchus mykiss). (November 2016) - Kutyrev, Ivan; Cleveland, Beth; Leeds, Timothy; Wiens, Gregory D.
Abstract: Flavobacterium psychrophilum ( Fp ) is the causative agent of bacterial cold water disease (BCWD) which causes appreciable economic losses in rainbow trout aquaculture. We previously reported development of a genetic line, designated ARS-Fp-R that exhibits higher survival relative to a susceptible line, designated ARS-Fp-S, following either laboratory or natural on-farm challenge. The objectives of this study were to determine the temporal kinetics of gene expression between experimentally-challenged ARS-Fp-R and ARS-Fp-S fish and the correlation between gene expression and pathogen load. We developed a GeXP multiplex RT-PCR assay to simultaneously examine expression of immune-relevant genes, concentrating on tumor necrosis factor and interleukin-1 ligand/receptor systems and acute phase response genes. Spleen tissue was sampled at 6 h, 24 h, 48 h and 144 h post-challenge and pathogen load quantified by qPCR. Transcript abundance of cytokine genes tnfa1, tnfa2, tnfa3, il1b1, il1b2, il11a ; acute phase response genes saa and drtp1 ; and putative cytokine receptors il1r1-like-b, il1r2, tnfrsf1a, tnfrsf9, tnfrsf1a-like-b increased following challenge while the transcript abundance of il1r-like-1 and tnfrsf1a-like-a decreased compared to PBS-injected line-matched control fish. Principal component analysis identified transcript levels of genes il1r-like-1 and tnfrsf1a-like-a as exhibiting differential expression between genetic lines. In summary, Fp i.p. injection challenge elicited a proinflammatory cytokine gene expression response in the spleen, with ARS-Fp-R line fish exhibiting modestly higher basal expression levels of several putative cytokine receptors. This study furthers the understanding of the immune response following Fp challenge and differences in gene expression associated with selective breeding for disease resistance. Graphical abstract: Image 1 Highlights: Multiplex RT-PCR assay developed that measures proinflammatory gene expression. Fp challenge increased expression of cytokines tnfa1, tnfa2, tnfa3, il1b1, il1b2, and il11a . Fp challenge increased expression of putative receptors il1r1-like-b, il1r2, tnfrsf1a, tnfrsf1a-like-b and tnfrsf9 . Fp challenge decreased expression of il1r-like-1 and tnfrsf1a-like-a genes. Cytokine receptor gene expression differentiated between genetic lines of rainbow trout.